Respuesta :
Answer:
AB-C^2 = 3x^3 + x^2 + 9
Step-by-step explanation:
Hi
AB = (x^2)*(3x+2)= 3x^3 + 2x^2
C^2= (x-3)^2 = x^2 - 9
So
AB-C^2 = 3x^3 + 2x^2 - x^2 + 9 = 3x^3 + x^2 + 9
The simplest form of AB-[tex]C^{2}[/tex] is [tex]3x^{3} +x^{2} +6x-9[/tex].
Step-by-step explanation:
Given,
A = [tex]x^{2}[/tex]
B = [tex]3x+2[/tex]
C = [tex]x-3[/tex]
To find,
AB-[tex]C^{2}[/tex]
Putting the values of A, B, C we get
AB-[tex]C^{2}[/tex]
= [tex]x^{2} (3x+2) - (x-3)^{2}[/tex]
= [tex]3x^{3} +2x^{2} -(x^{2} -6x+9)[/tex]
= [tex]3x^{3}+2x^{2} -x^{2} +6x-9[/tex]
=[tex]3x^{3} +x^{2} +6x-9[/tex]
Here is the answer.